1990
DOI: 10.1159/000216147
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Thrombolytic Properties of Fibrolase -A New Fibrinolytic Protease from Snake Venom

Abstract: Fibrolase, a direct-acting fibrinolytic enzyme has been shown to cleave primarily the Aα and Bβ chains of human fibrin. We have previously reported that fibrolase also exhibits fibrinogenolytic activity and acts mainly as an α-chain fibrinogenase. In contrast to the action of streptokinase (plasminogen activator), fibrolase does not activate plasminogen. In vitro thrombolytic efficacy of fibrolase was determined by monitoring the release of radiolabel from iodinated fibrin and human blood clots. Fibrolase effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Recent interest has been generated in snake venom direct-acting fibrinolytic metalloproteinases because of their clinical potential for the treatment of occlusive vascular disease. Several of these enzymes have been tested in vivo with promising results (23,47,55,77,79,101). These studies revealed that the highly purified fibrinolytic snake venom enzymes produced consistent thrombolysis.…”
mentioning
confidence: 99%
“…Recent interest has been generated in snake venom direct-acting fibrinolytic metalloproteinases because of their clinical potential for the treatment of occlusive vascular disease. Several of these enzymes have been tested in vivo with promising results (23,47,55,77,79,101). These studies revealed that the highly purified fibrinolytic snake venom enzymes produced consistent thrombolysis.…”
mentioning
confidence: 99%
“…On the other hand, using an animal model of arterial thrombosis, fibrolase dissolves femoral arterial clots after a single intravenous bolus administration. These data revealed the potential of this fibrinolytic enzyme to treat occlusive thrombotic disease, but the problem was that fibrolase is not a plasminogen activator [66]. Therefore, an alternative strategy is to produce a chimeric derivative from fibrolase that possesses the dual ability to degrade fibrin clots and to inhibit platelet aggregation and thrombus reformation.…”
Section: Fibrinolytic Enzyme Activitymentioning
confidence: 99%
“…Among the fibrinolytic P-I SVMPs with potential as thrombolytic therapeutics, fibrolase from A. c. contortrix has been documented to have strong fibrinolytic activity in vitro [70,71]. In addition, the enzyme has been tested in experimental rabbit [72] and canine [73] animal model systems as a thrombolytic agent against artificially created thrombi.…”
Section: P-i Class Svmps As Potential Thrombolytic Enzymesmentioning
confidence: 99%